HUBUNGAN FAKTOR INTERNAL INSTITUSI DAN IMPLEMENTASI SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) DI PEMERINTAH DAERAH - Sofyani, Hafiez; Akbar, Rusdi (UI Scholars Hub, 2013)
The purpose of this study was to examine the association between technical, organizational, individual characteristics of local government officials factors and the implementation of performance measurement systems (PMS) in local government. The study was conducted in territory of local government of Yogyakarta Special Region (DIY). The samples are local government officials in Satuan Kerja Perangkat Daerah (SKPD) who are directly involved in the implementation of the Performance Accountability System for Government Entity (SAKIP) and reporting Performance Accountability Reports for Government Entity (LAKIP). The results found the factors that positively and significantly associated with implementation of a PMS were organizational factors, namely: training and organization’s response are open to change, and the individual characteristics factors, namely: high self-efficacy and conscientiousness trait.